(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: The idea of the current study revolves around identifying the level of intellectual security among professors at the University of Mosul in light of the National Security Strategy (2025–2030), from their perspective Objective: The study seeks to assess intellectual security among faculty members at the University of Mosul and determine its level according to academic rank. Methodology: The study adopted a descriptive-analytical approach. The sample consisted of 250 male and female faculty members from the University of Mosul for the academic year 2025–2026. To achieve the research objective, the researchers developed a 40-item questionnaire, whose validity and reliability were verified. The instrument was administered to faculty members from several colleges of the University of Mosul and the Regional Studies Center. Data were analyzed using Pearson’s correlation coefficient, percentages, the z-test for two independent samples, and the Statistical Package for the Social Sciences (SPSS). Results: The level of intellectual security among participants holding the academic rank of Professor reached 76.74%, which is considered a good level. Among Assistant Professors, the level reached 68.84%, which is close to a good level. Among Lecturers, the level reached 71.06%, which is considered a good level. Among Assistant Lecturers, the level reached 68.90%, which is also close to a good level. The results indicated that there were no statistically significant differences in intellectual security among University of Mosul faculty members according to academic rank (Professor, Assistant Professor, Lecturer, Assistant Lecturer). The researchers further presented a set of conclusions, recommendations, and proposals.